Perancangan Strategi Visual Branding C&F Laundry Service Cerme, Gresik Secara Online Saat Pandemi Covid-19 - Cindy Muljosumarto; Stephanie Jessica; Joan Jona Naftali (LPPM Stikosa - AWS, 2022)
Covid-19 has changed and affecting all industries including the dynamic of MSME industries, which keep emerging during pandemic. C&F Laundry Service Cerme, is a MSME that has been establish quite long ago, but since there are more competitors than before, C&F Laundry needs to have a proper branding strategy to stand out and gain more brand awareness. Therefore, we collaborate with C&F Laundry to create a branding strategy, starting with the visual branding that can give solution for the problem. We used quantitative method and because of pandemic situation, most of the works was done via online meeting with the active participation and contribution from C&F Laundry owner. Our method was, observing the problem using in depth interview, observing the competitors and target audience with sampling technique, then analyze using branding theory and create concept for the visual branding design. The results are brand book guideline for the new brand, which applied to the interior and exterior design of the shop building and social media for the brand activation.